Diverse opnamen van het stuk 'Morgen komt Mira' van theatergroep Diskus. Op een aantal banden ook Chili dia's
Diverse opnamen van het stuk 'Morgen komt Mira' van theatergroep Diskus. Op een aantal banden ook Chili dia's.